Women Offenders Under Community Supervision: Comparing the Profiles of Returners and Non-Returners to Federal Prison - McKendy, Laura; Ricciardelli, Rosemary (Frontiers in Psychiatry, 2019)
As a key indicator of correctional performance, returns to custody are a topic of much empirical inquiry, yet there remains considerable debate regarding questions around who returns and why, as well as the factors that support or impede successful post-release outcomes. Research examining the post-release trajectories of federal releasees in the Canadian context, particularly in the case of women, is necessary to identify opportunities for more responsive case management practices. Drawing on the case files of 43 formerly-federally-incarcerated women referred to a day reporting centre in a large Canadian city, we explore the profiles of women who returned to federal custody from those who did not, considering factors related to demographics, personal history, specifically mental health and mental health needs, static risk and dynamic need. In general, we found that those who returned to custody tended to have more needs and more complex needs relative to non-returners. Notable differences were evident in relation to criminal history, reintegration potential, dynamic factor needs, the presence of a mental health condition, the presence of substance addiction and institutional adjustment (as measured by institutional charges and segregation placements). While not attempting to present causal relationships, we shed light on the case management needs of this particular group and identify areas in need of further inquiry.